Rich stoichiometries of stable Ca-Bi system: Structure prediction and superconductivity - Dong, Xu; Fan, Changzeng (Scientific reports, 2015)
Using a variable-composition ab initio evolutionary algorithm implemented in the USPEX code, we have performed a systematic search for stable compounds in the Ca-Bi system at different pressures. In addition to the well-known tI 12-Ca 2 Bi and oS 12-CaBi 2 , a few more structures were found by our calculations, among which phase transitions were also predicted in Ca 2 Bi ( tI 12 → oI 12 → hP 6), Ca 3 Bi 2 ( hP 5 → mC 20 → aP 5) and CaBi ( tI 2 → tI 8), as well as a new phase (Ca 3 Bi) with a cF 4 structure. All the newly predicted structures can be both dynamically and thermodynamically stable with increasing pressure. The superconductive properties of cF 4-CaBi 3 , tI 2-CaBi and cF 4-Ca 3 Bi were studied and the superconducting critical temperature T c can be as high as 5.16, 2.27 and 5.25 K, respectively. Different superconductivity behaviors with pressure increasing have been observed by further investigations.